Efektivitas Perasan Daun Kemangi (Ocimum basilicum) dibanding Larutan Pembersih Gigi Tiruan Effervescent sebagai Pembersih Gigi Tiruan Resin Akrilik terhadap Pertumbuhan Candida albicans - Sherlika Puspita Sari; Achmad Gunadi; Dewi Kristiana (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
The heat cured acrylic resin is common used as denture base material, but its microporosity can affect the cleanliness of the denture base lead to accumulation of plaque and food waste, and further increase the number of Candida albicans and cause denture stomatitis. There are 2 type of cleaning agents; natural cleaning agents, such as basil and chemical cleaning agents, for example effervescent artificial cleaning tablets. This study compared the effectiveness of basil leaves squeeze and effervescent denture cleaning solutions in soaking heat cured acrylic resin plates on the growth of C. albicans. There were 24 of 10x10x1 mm acrylic resin plates divided into 6 treatment groups. The acrylic resin plate was soaked in the basil leaves squeeze and effervescent denture cleaning solutions. Measurement of C. albicans absorbance used a spectrophotometer, then calculated the total of C. albicans using the formula. Data was analyzed using the One Way ANOVA test. The analysis showed that there are significant differences on the growth inhibition of C. albicans between treatment groups (p <0.005). The effervescent denture cleansing solution has a better antifungal effectiveness than the basil leaves